2016
DOI: 10.1017/s1355617716000606
|View full text |Cite
|
Sign up to set email alerts
|

Time Perception in Mild Cognitive Impairment: Interval Length and Subjective Passage of Time

Abstract: Objectives: Patients with mild cognitive impairment (MCI) may have difficulties in time perception, which in turn might contribute to some of their symptoms, especially memory deficits. The aim of this study was to evaluate perception of interval length and subjective passage of time in MCI patients as compared to healthy controls. Methods: Fifty-five MCI patients and 57 healthy controls underwent an experimental protocol for time perception on interval length, a questionnaire for the subjective passage of tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
27
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(30 citation statements)
references
References 42 publications
2
27
1
Order By: Relevance
“…We did not observe temporal impairment in MCI patients, a result consistent with previous studies (Rueda and Schmitter-Edgecombe, 2009; Coelho et al, 2016), although surprising considering that temporal impairment is often observed in healthy older adults either when they are required to process neutral stimuli (Block and Zakay, 1997; Block et al, 1998; Turgeon et al, 2016; Lamotte and Droit-Volet, 2017) or when temporal intervals are marked by emotional stimuli (Nicol et al, 2013). Indeed, several studies have found age-related differences in time estimation and have related them to either variation at the level of the internal clock or age-related changes in the cognitive processes involved in time estimation.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…We did not observe temporal impairment in MCI patients, a result consistent with previous studies (Rueda and Schmitter-Edgecombe, 2009; Coelho et al, 2016), although surprising considering that temporal impairment is often observed in healthy older adults either when they are required to process neutral stimuli (Block and Zakay, 1997; Block et al, 1998; Turgeon et al, 2016; Lamotte and Droit-Volet, 2017) or when temporal intervals are marked by emotional stimuli (Nicol et al, 2013). Indeed, several studies have found age-related differences in time estimation and have related them to either variation at the level of the internal clock or age-related changes in the cognitive processes involved in time estimation.…”
Section: Discussionsupporting
confidence: 92%
“…Specifically, we tested MCI patients during a time bisection task to investigate temporal impairment in these patients. If the results observed by Mioni et al (2016b) with PD with MCI were mainly driven by their cognitive impairment, we should observe a leftward shift of the psychometric function (indicating temporal overestimation) and higher temporal variability in MCI patients compared to controls; however, this is not what was observed in previous studies (Rueda and Schmitter-Edgecombe, 2009; Coelho et al, 2016). Two finger-tapping tasks (spontaneous rate and 1 s rate) were included considering that spontaneous-tempo measure has been related to the pace of the internal clock (Pouthas and Perbal, 2004; Perbal et al, 2005; Jones and Jahanshahi, 2009).…”
Section: Introductioncontrasting
confidence: 65%
See 1 more Smart Citation
“…These studies showed that AD patients had an impairment in time processing and they had significant alterations in the judgment of time duration [11]. Only few studies have investigated time perception in mild cognitive impairment (MCI) and they reported normal findings [6,12]. Conversely, there is evidence that the subjective experience of time is altered even at the early stage of cognitive impairment (MCI) [12].…”
Section: Introductionmentioning
confidence: 99%
“…Only few studies have investigated time perception in mild cognitive impairment (MCI) and they reported normal findings [6,12]. Conversely, there is evidence that the subjective experience of time is altered even at the early stage of cognitive impairment (MCI) [12].…”
Section: Introductionmentioning
confidence: 99%